Three new goatfishes of the genus Upeneus from the Eastern Indian Ocean and Western Pacific, with an updated taxonomic account for U. itoui (Mullidae: japonicus-species group) - Uiblein, Franz; Motomura, Hiroyuki (Zootaxa, 2021)
Coastal marine fish diversity from E India and Indonesia to S Japan is still insufficiently investigated. Of the 42 species of goatfishes (Mullidae) recorded from this area, 12 were described only since 2010 and ten of those belong to the genus Upeneus. During a recent review of species of Upeneus of the so-called japonicus-species group (characterized by seven dorsal-fin spines), 13 specimens that had been previously identified as U. guttatus from Indonesia and Vietnam were found to be distinct, representing possibly two undescribed species. These specimens were studied together with 20 U. itoui from S Japan, a rather similar species, and a yet unidentified congeneric from S Japan. In total 41 morphometric, 10 meristic and several colour characters were examined and detailed comparisons with a large data set from all 14 japonicus-group species conducted. Three new species, U. dimipavlov n. sp. from Nha Trang, S-central Vietnam, U. elongatus n. sp. from Tanega-shima Island, Kagoshima, S Japan and U. willwhite n. sp. from Lombok, S Indonesia are described and an updated account for U. itoui is provided. Among these four featured species, U. elongatus is the most different, having more gill rakers, the shallowest head and body and distinct colour patterns on caudal and dorsal fins. Upeneus dimipavlov differs from the remaining two species in having a more rounded and less laterally compressed body with a wider caudal peduncle and no conspicuous mid-lateral body stripe in fresh fish. Upeneus willwhite differs from U. itoui in deeper head, larger eyes, longer upper jaw and barbels and oblique bars on the lower caudal-fin lobe which do not cross the entire lobe. Additional comparisons of each of the four featured species with all other japonicus-group species and U. heterospinus were conducted providing evidence for distinction and differential diagnosis. Unvouchered in-situ photographs of four goatfish specimens from the Central Philippines that resemble U. elongatus in caudal- and dorsal-fin colour patterns are presented. The need for further sampling and associated taxonomic investigations as prerequisites for appropriate assessment of ecological and conservation parameters such as diversity, distribution and rarity is emphasized in the discussion.